Motion of water monomers reveals a kinetic barrier to ice nucleation on graphene - Tamtögl, Anton; Bahn, Emanuel; Sacchi, Marco; Zhu, Jianding; Ward, David J.; Jardine, Andrew P.; Jenkins, Stephen J.; Fouquet, Peter; Ellis, John; Allison, William (Nature Communications, 2021)
The interfacial behaviour of water remains a central question to fields as diverse as protein folding, friction and ice formation. While the properties of water at interfaces differ from those in the bulk, major gaps in our knowledge limit our understanding at the molecular level. Information concerning the microscopic motion of water comes mostly from computation and, on an atomic scale, is largely unexplored by experiment. Here, we provide a detailed insight into the behaviour of water monomers on a graphene surface. The motion displays remarkably strong signatures of cooperative behaviour due to repulsive forces between the monomers, enhancing the monomer lifetime ( ≈ 3 s at 125 K) in a free-gas phase that precedes the nucleation of ice islands and, in turn, provides the opportunity for our experiments to be performed. Our results give a molecular perspective on a kinetic barrier to ice nucleation, providing routes to understand and control the processes involved in ice formation.